Renal L-2-hydroxyglutarate dehydrogenase activity promotes hypoxia tolerance and mitochondrial metabolism in Drosophila melanogaster - Nader H. Mahmoudzadeh; Yasaman Heidarian; Jason P. Tourigny; Alexander J. Fitt; Katherine Beebe; Hongde Li; Arthur Luhur; Kasun Buddika; Liam Mungcal; Anirban Kundu; Robert A. Policastro; Garrett J. Brinkley; et al. (Elsevier, 2024)
Objectives: The mitochondrial enzyme L-2-hydroxyglutarate dehydrogenase (L2HGDH) regulates the abundance of L-2-hydroxyglutarate (L-2HG), a potent signaling metabolite capable of influencing chromatin architecture, mitochondrial metabolism, and cell fate decisions. Loss of L2hgdh activity in humans induces ectopic L-2HG accumulation, resulting in neurodevelopmental defects, altered immune cell function, and enhanced growth of clear cell renal cell carcinomas. To better understand the molecular mechanisms that underlie these disease pathologies, we used the fruit fly Drosophila melanogaster to investigate the endogenous functions of L2hgdh. Methods: L2hgdh mutant adult male flies were analyzed under normoxic and hypoxic conditions using a combination of semi-targeted metabolomics and RNA-seq. These multi-omic analyses were complemented by tissue-specific genetic studies that examined the effects of L2hgdh mutations on the Drosophila renal system (Malpighian tubules; MTs). Results: Our studies revealed that while L2hgdh is not essential for growth or viability under standard culture conditions, L2hgdh mutants are hypersensitive to hypoxia and expire during the reoxygenation phase with severe disruptions of mitochondrial metabolism. Moreover, we find that the fly renal system is a key site of L2hgdh activity, as L2hgdh mutants that express a rescuing transgene within the MTs survive hypoxia treatment and exhibit normal levels of mitochondrial metabolites. We also demonstrate that even under normoxic conditions, L2hgdh mutant MTs experience significant metabolic stress and are sensitized to aberrant growth upon Egfr activation. Conclusions: These findings present a model in which renal L2hgdh activity limits systemic L-2HG accumulation, thus indirectly regulating the balance between glycolytic and mitochondrial metabolism, enabling successful recovery from hypoxia exposure, and ensuring renal tissue integrity.